2015
DOI: 10.1111/dar.12274
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and motives of pre‐drinking with intoxication and harm around licensed venues in two cities

Abstract: 'Pre-drinking' was normal behaviour in the current sample and contributes significantly to the burden of harm and intoxication in the NTE. Price disparity between packaged vs. venue liquor is a key motivator for pre-drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 23 publications
6
35
0
Order By: Relevance
“…Relative to the large number of studies conducted on pre‐gaming in the US and UK, there is little research on pre‐gaming in Australia or New Zealand. The limited research that has been conducted in Australia is consistent with international research suggesting that pre‐gaming is commonplace, 20 that price is a key motivation for pre‐gaming 20–22 and that pre‐gaming is associated with greater odds of experiencing alcohol‐related harms 20,21,23,24 . Research in New Zealand is even more limited, with (to our knowledge) only a single study investigating pre‐gaming 25 .…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Relative to the large number of studies conducted on pre‐gaming in the US and UK, there is little research on pre‐gaming in Australia or New Zealand. The limited research that has been conducted in Australia is consistent with international research suggesting that pre‐gaming is commonplace, 20 that price is a key motivation for pre‐gaming 20–22 and that pre‐gaming is associated with greater odds of experiencing alcohol‐related harms 20,21,23,24 . Research in New Zealand is even more limited, with (to our knowledge) only a single study investigating pre‐gaming 25 .…”
supporting
confidence: 64%
“…To help find this balance, universities could consult students in policy discussions 31 . This recommendation is offered while acknowledging that the price differential between on‐ and off‐licence liquor sales is considered a core motive for pre‐gaming behaviour, particularly among university students where income can be limited 20,32 . As such, measures to address the price gap between on‐ and off‐licence liquor are also likely to influence pre‐gaming behaviour, especially for this cohort 5,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a moderately developed literature base outlining the relationship between pre-drinking, intoxication, and harm. For instance, one of our previous studies using a similar method in two Australian cities found that compared with non-predrinkers, patrons who had consumed 6-10 standard pre-drinks were 1.5 times more likely to be involved in a violent incident in the past 12 months, increasing to 1.8 times more likely for patrons who had consumed 11-15 drinks [18]. Similarly, we found pre-drinking to be the strongest correlate of intoxication out of a range of variables [40].…”
Section: Alcohol Consumption and Pre-drinkingmentioning
confidence: 99%
“…The dose-dependent relationship between alcohol intoxication and subsequent impairment is well established, with epidemiological research showing that risk of alcohol-related injury increases linearly with increasing intake [4]. Of concern, recent research has shown that drinking prior to attending nighttime entertainment districts ('pre-drinking' or 'pre-loading') may be associated with greater alcohol intake and greater likelihood of involvement in alcohol-related violence [5][6][7]. Consumption of energy drinks with alcohol has also been shown to increase likelihood of engaging in some risky behaviours by reducing perception of intoxication [8,9] (although see [10] for contradictory findings), with a strong body of literature also showing greater impairment and acute harms following co-ingestion of alcohol and other illicit drugs (hereafter referred to as 'simultaneous' use [11][12][13]).…”
Section: Introductionmentioning
confidence: 99%